COMPARATIVE EFFICACY OF SOME INSECTICIDES AGAINST COTTON WHITEFLY, BEMISIA TABACI (GENNADIUS) (HOMOPTERA: ALEYRODIDAE) UNDER NATURAL FIELD CONDITIONS - Hasnain, M.; Nadeem, M. K.; Ahmed, S.; Ashfaq, M.; Nadeem, S. (The Nucleus, 2011)
Comparative efficacy of five commonly used insecticides viz., acetamiprid, buprofezin, diafenthiuron, imidacloprid and endosulfan against nymph and adult population of cotton whitefly, Bemisia tabaci (Gennadius) (Homoptera: Aleyrodidae) under natural field conditions has been studied. Results showed that buprofezin was the most effective insecticide against nymph population of whitefly among the tested insecticides where nymphal population of B. tabaci was 0.2/leaf after 24h spray as compared to 1.9/leaf in control. Acetamiprid was the most effective against adult population of whitefly (0.3 to 1.3/leaf post 72 h spray, as compared to control with 6.9 to 8.2/leaf) followed by diafenthiuron and imidaclopirid. whereas, endosulfan was found to be the least effective on both populations as adult and nymph of whitefly. From the tested insecticides, acetamaprid gave effective control of both nymph and adult population of B. tabaci.